Pre-workout supplementation of capsaicin does not increase resistance training performance in a multiexercise protocol in trained men - Igor C.S. Fonseca; Vernon M. Cruz; Mariana Fonseca; Ronaldo A.D. Silva; Carolina B. Simões; Pau la L.C. Gomes; Marcos D.M. Drummond (Termedia Publishing House, 2023)
Purpose The aim of this study was to investigate the acute effect of capsaicin supplementation on performance, perceived exertion, and perceived effects in a resistance training protocol for the lower body. Methods The sample was 14 young men (22.21 ± 2.55 years; 82.35 ± 5.16 kg; 174 ± 0.7 cm; 9.08 ± 2.73% of body fat), with 4.19 ± 2.98 years of experience in resistance training. The study design was randomised, double-blind and crossover. The subjects performed the training protocol after consuming Capsaicin (12 mg) (CAP) or a placebo (PLA). The training protocol was: five sets of Back Squats and Leg Presses 45°, with 70% of 1RM until failure. The interval between sets was 90 seconds and 120 seconds between exercises. The number of maximum repetitions (NMR) and the rate of perceived exertion (RPE) were recorded after each set. Results The paired t-test showed that there was no statistically significant difference between PLA and CAP in the mean NMR ( p = 0.251; 95%CI = -5.47 - 19.18), mean session volume load (VL) (weight lifted × NMR) ( p = 0.117; 95%CI = -582.70 - 4639.99) and in the mean RPE ( p = 0.458; 95%CI = -0.81 - 0.39). Conclusions The acute capsaicin supplementation did not change the perception of vigour and side effects. Therefore, pre-workout capsaicin supplementation did not alter performance, RPE, or perceived effects in a lower body multi-exercise training protocol in trained men.